Analysing the Policies of the First Three Kings of the Davidic Dynasty - Seheno, Randrialiva Soanirina; Baholy, Robijaona Rahelivololoniaina (Budapest International Research and Critics University, 2025)
This publication exposes in a simple and relevant way the policies of the first three kings of the Davidic dynasty. These kings had different perspectives but were able to change the future of their nation in their respective ways. David used power in order to make his people free from the pagan nations; Solomon ruled wisely to enrich and place Israel in the same level of the great nations around them; and Rehoboam wished to have more power and authority than his ancestors and tried to find another policy to govern Israel. But in any case, their ways of governing marked the story of Israel. This research will help us to understand the reason for the success and defeat of these kings, so that we can learn from them for a better future.